Democracy and crisis democratising governance in the twenty-first century - Isakhan, Benjamin; Slaughter, Steven; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Recent years have seen constant reports on the failures of governance and the crisis of democracy. By examining cases like Global Financial Crisis, the Arab Revolutions and Wikileaks this volume highlights tensions between governance and democracy during times of crisis and examines the prospects of democratising governance in the 21st Century.
Keywords: Political science; Political theory; Democracy; Public policy; Political philosophy; Political sociology; Political Science and International Relations; Political Science; Political Sociology; Political Theory; Political Philosophy; Public Policy; Democracy